2017
DOI: 10.29121/granthaalayah.v5.i8(se).2017.2285
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Work-Life Balance of Nursing Staff Working in Private Hospitals in Palayamkottai

Abstract: At present every successful employee has to pass through the dilemma of work life balance in personal and professional life. For the sake of leading a successful life, people do not hesitate to give extra time for achieving the objectives of life. In the process of getting extra mileage in their professional life they have to make a lot of compromise and sometimes mental piece also gets distorted. We have 24 hours at our disposal to deal with and it is up to us how to schedule and plan the same. It is rightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…15 WLB is not only important for job satisfaction but also for organization commitment and retention at workplacewhich may positively impact upon the job performance. 5,18 The study shows no association between WLB with sociodemographic variable such as age, ethnicity and educational level where as a study from Malaysia had shown educational level playing significant roles in determining association with the WLB.Educational level has also affected nurses physically, psychologically and socially. 3 In the family variable, WLB was significantly associated with the type of family (p=0.03) and number of earning members in the family (p=0.04).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…15 WLB is not only important for job satisfaction but also for organization commitment and retention at workplacewhich may positively impact upon the job performance. 5,18 The study shows no association between WLB with sociodemographic variable such as age, ethnicity and educational level where as a study from Malaysia had shown educational level playing significant roles in determining association with the WLB.Educational level has also affected nurses physically, psychologically and socially. 3 In the family variable, WLB was significantly associated with the type of family (p=0.03) and number of earning members in the family (p=0.04).…”
Section: Discussionmentioning
confidence: 87%
“…WLB is termed as an essential factor. [3][4][5] Introduction: Work-Life Balance (WLB) is defined as a degree to which a person is engaged in and satisfied with their work, family and social life. The objective of this study was to assess the level of WLB among nurses working in tertiary level hospital and to measure the association between independent variables and level of WLB.…”
mentioning
confidence: 99%
“…Similarly, Sharma S et al ( 2018) conducted a study on work-life balance among 141 doctors and 216 nurses in government hospitals of Himachal Pradesh and found that doctors and nurses use more leave arrangements, particularly cultural/religious leave (60% and 78%) and pooling of leave entitlements (67% and 62%) respectively [4]. Nowadays due to the spread of globalization, technological advancements, and a highly competitive work environment, every successful employee encounters the difficulty of striking a balance between their personal and professional lives [5]. Stress and extended work hours can be major causes of burnout in certain work environments, which can ultimately lead to increased absenteeism, workplace aggression, and workers' compensation claims [6].…”
Section: Introductionmentioning
confidence: 99%